Relationship Between Motivation and Performance of Posyandu Cadres - wijayanti, Novi; Vanchapo, A.R; Darmayanti, Aquartuti Tri (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Motivation is a process that occurs in a person that appears with feelings so that it encourages individuals to do something caused by one's desires, needs and goals. The performance of cadres can be seen from the success of a cadre in carrying out their duties. To improve the performance of posyandu cadres, the ability of a cadre must be developed. The purpose of this study was to determine the relationship between work motivation and the performance of posyandu cadres. The database used in the Literature review is Google Scholar with sample inclusion criteria, articles published in the last 5 years, using national journals, articles using the correlational method with the population used are Posyandu cadres. The search for journals in this study used the search keyword